The Effect of Depression on Study Results of Public University Students in Thailand - Ounprasertsuk, Jatuporn; Benjanirat, Tipvarin; Wongpituk, Karnarong; Tayaman, Suwimon (International Journal of Psychosocial Rehabilitation, 2020)
The concept of bullying can be defined as the set of acts in which the students that are physically, mentally and socially strong put pressure on their weaker fellows and abuse them. In the same way, bullying has also been taken in the context that a student when repeatedly faces negative behavior from other fellow students, it will also be taken in the category of bullying. These types of bullies might impact the students in one way or the other. In the similar context, the researcher has designed this study to explore the three types of school bullying i.e. physical, verbal and relational bullying on the perceived academic performance of the students of universities in Thailand along with the mediating role of depression in the students. For analysis purpose, the researcher has collected data from the students of these universities through online questionnaire administration and the results have been obtained through statistical analysis. The results have shown that that all the independent variables have significant and negative impact on the dependent variable of the study. In other words, with the increase of physical, verbal and relational bullying, the academic performance of the students will be decreased dramatically. In addition to this, the mediating role of depression has also been found as significant in all three relationships.